Assistance in activities of the Association of Veteran Wives of the Republic of Indonesia (PIVERI) in Banyuwangi Regency: Pendampingan Kegiatan Organisasi Persatuan Istri Veteran Republik Indonesia (PIVERI) di Kabupaten Banyuwangi - Miskawi (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
The Association of Wives of Veterans of the Republic of Indonesia or PIVERI is an organization consisting of wives of Veterans of the Republic of Indonesia. One of PIVERI's routine activity agendas is the commemoration of birthdays, which in 2024 will enter its 60th year. Accompanying ceremonial activities, flower sowing which begins with a ceremony at the hero's cemetery, thanksgiving events and free medical treatment are carried out as community service. Assistance includes organizing events, especially event planning and personnel assistance. Lecturers together with students from the History Education Study Program at PGRI Banyuwangi University helped organize the event. This assistance is a continuation of similar activities carried out with veterans.